Penanganan Kasus Perundungan Di Pondok Pesantren Anak-Anak - Ali Mastur (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2021)
Bully in English means bully, someone who likes to bother other people, someone who likes to get angry. The term Bully is also very close to the Indonesian term, namely violence. Usually bullying occurs due to several factors such as the victim being weak, having no class, having a physical illness/disability or mental disability. Based on these factors, bullies usually use the victim's shortcomings to carry out acts of bullying. Therefore, this research aims to analyze the handling of bullying cases at the Assalafi Al Fithrah Islamic Boarding School for Children in Surabaya. Research using qualitative methods found that the bullying that often occurs is verbal or verbal bullying, but not often physical bullying. And the role of the Management in handling cases of bullying that occur is very important and vital. Apart from carrying out their duties and roles, administrators also function as companions, supervisors and providers of punishment or consequences for students who commit acts of bullying, as well as providing advice, guidance and direction as appropriate (in accordance with the rules and regulations). And there are several factors that cause bullying cases, including: family factors, child factors, and social environmental factors.